Hybridisation of chlorophenoxyherbicides with layered double hydroxide for the formation of layered organic-inorganic encapsulated agrochemical nanocomposites. - Sarijo, Siti Halimah; Hussein, Mohd. Zobir; Zainal, Zulkarnain (Inderscience Publishers, 2010)
Agrochemicals of phenoxyherbicides-type, namely 2-chlorophenoxyacetate (2CPA) and 2,4,5 trichlorophenoxyacetate (TCPA) were encapsulated separately into zinc-aluminium-layered double hydroxide inorganic interlamellae for the formation of new organic-inorganic hybrid nanocomposites materials, N2CPA and NTCPA, respectively. Intercalation of the organic moieties was accomplished by self-assembly method. Well-ordered nanolayered structure of the nanocomposites were obtained at pH 7.5 with Zn to Al molar ratio, Ri = 2 using 0.2 M 2CPA and Ri = 4 with 0.4 M TCPA, respectively. The expansion of basal spacing from 8.9 Å in the layered double hydoxide with nitrate as the counter anion to 18.5 and 26.4 Å in the resulting nanocomposites, N2CPA and NTCPA respectively was observed. Molar ratios of Zn to Al, R for both the as-synthesised nanocomposites are close to their respective initial molar ratio of the mother liquor, Ri with loading percentage of 2CPA and TCPA is 34.8 and 53.3% respectively.